PRESTASI BELAJAR MAHASISWA PGSD STKIP MELAWI ENTIKONG DITINJAU DARI ASPEK KOGNITIF MASA PANDEMI COVID-19 - Fransisco Adam (Universitas Tanjungpura, 2023)
This study the aims to describe student learning achievement in terms of cognitive aspects during the covid-19 pandemic. The is research method is a case study with a descriptive qualitative approach. The research subjects were PGSD Melawi Entikong students in the even semester of the 2021 academic year. The data collection technique used a test technique while the instrument was a test question in the form of an essay. Data analysis was carried out on the results of essay questions that focused on cognitive aspects. The results showed; (1) this level of mastery of aspects of factual knowledge the is specifically on aspects of that cognitive processes, namely remembering that consists of recognizing/identifying, recalling by 45%, while other aspects such as C2 to C6 are still zero percent. level of mastery; (2) level of mastery of conceptual knowledge aspects of cognitive process dimensions consisting of interpreting, exemplifying, clarifying, summarizing, concluding, comparing, and explaining by 45% while 10% of cognitiveaspects of analyzing and C1, C3, C5, and C6 are still zero percent ; (3) the level of mastery of procedural knowledge aspects, especially aspects of cognitive processes, namely applying 35% which includes implementing, using and 20% of creating cognitive dimensions consisting of formulating, planning, and producing other aspects is still zero percent; (4) the level of mastery of aspects of metacognitive knowledge. Especially aspectsof cognitive processes, namely implementing includes implementing and using 25% and other aspects zero percent. The conclusion is that student learning achievement in terms of the cognitive aspect is still is very low, this is due to limited conditions, processes, and learning methods due to covid-19. The government's suggestion is to immediately make efforts so that the learning process can return to normal and restore learning in essence.